Effects of feeding male and female broiler chickens on low-protein diets fortified with different dietary glycine levels under the hot and humid tropical climate - Mohamed, Elmutaz Atta Awad; Idrus, Zulkifli; Farjam, Abdoreza Soleimani; Aljuobori, Ahmed (Taylor & Francis, 2017)
This study was conducted to evaluate the effect of sex and level of glycine (Gly) fortification to low-protein diets on growth performance, selected serum metabolites, carcass yield and litter characteristics in broiler chickens under tropical climate. Day-old male (n = 400) and female (n = 400) broiler chicks were assigned to five isocaloric diets (positive control, PC; negative control, NC; and more three diets obtained by fortifying NC diet with higher Gly concentrations). No significant diet × sex interaction was observed for all the parameters measured. Comapered to NC group, weight gain (WG) significantly increased (p<.0001) by feeding Gly fortified low-CP diets throughout the experiment; however, WG and feed intake (FI) of birds fed NC or NC + Gly diets were significantly lower (p<.0001) compared to PC group. During the overall period, fortification of NC diet with Gly significantly improved (p<.0001) the feed conversion ratio (FCR) compared to NC group, and resulted in FCR similar to those birds fed the PC diet. Diet effect was significant (p<.0001) for performance parameters, proportional liver and abdominal fat weights, serum triglycerides (TG) and uric acid (UA) and litter moisture and nitrogen contents; with no Gly level effect (linear and quadratic, p > .05). The sex effect was significant for performance parameters, abdominal fat, and litters’ moisture and nitrogen contents. In conclusion, it is likely that additional Gly fortification to low-CP diets under tropical climate may have a better effect on broiler chickens after the starter phase. Moreover, feeding Gly fortified low-CP diets may improve the FCR and reduce the nitrogen excretion.